Patterns of cortisol and corticosterone concentrations in humpback whale (Megaptera novaeangliae) baleen are associated with different causes of death. Issue 1 (23rd December 2021) - Lowe, Carley L; Hunt, Kathleen E; Robbins, Jooke; Seton, Rosemary E; Rogers, Matthew; Gabriele, Christine M; Neilson, Janet L; Landry, Scott; Teerlink, Suzie S; Buck, C Loren
Abstract: Baleen whales are subject to a myriad of natural and anthropogenic stressors, but understanding how these stressors affect physiology is difficult. Measurement of adrenal glucocorticoid (GC) hormones involved in the vertebrate stress response (cortisol and corticosterone) in baleen could help fill this data gap. Baleen analysis is a powerful tool, allowing for a retrospective re-creation of multiple years of GC hormone concentrations at approximately a monthly resolution. We hypothesized that whales that died from acute causes (e.g. ship strike) would have lower levels of baleen GCs than whales that died from extended illness or injury (e.g. long-term entanglement in fishing gear). To test this hypothesis, we extracted hormones from baleen plates of four humpback whales ( Megaptera novaeangliae ) with well-documented deaths including multiple and chronic entanglements ( n = 1, female), ship strike ( n = 2, male and female) and chronic illness with nutritional stress ( n = 1, male). Over 3 years of baleen growth and during multiple entanglements, the entangled whale had average corticosterone levels of 80–187% higher than the other three whales but cortisol levels were similar to two of the other three whales. The nutritionally stressed and chronically ill whale showed a slow increase in both cortisol and corticosterone spanning 3 years, followed by a sharp decline in both hormones before death, possibly indicative of adrenal failure in this moribund individual. This whale's correlation between cortisol and corticosterone was significant but there were no correlations in the other three whales. Our results show that cortisol and corticosterone concentrations vary according to the type and duration of illness or injury. Single-point GC concentrations should be interpreted with caution as low values can occur in whales experiencing pronounced stress and individual baselines can be highly variable. Baleen analysis is a promising tissue type for retrospective analyses of physiological responses to various stressors affecting baleen whales.